Patterns of ephedra and other stimulant use in collegiate hockey athletes - Bents, R. T.; Marsh, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study examined trends in stimulant use and attitudes toward use among American collegiate hockey athletes. All 139 players in one college hockey conference completed a comprehensive questionnaire. Over half of the athletes (51.8%) confirmed stimulant use before a hockey game or practice. About half of the respondents (48.5%) reported having used ephedra at least one time to improve athletic performance. Additionally, 17.4% reported using pseudoephedrine to improve performance in the 30 days prior to survey administration. Over half (55.4%) were aware of the recent national ban on ephedra. Fifty-nine percent stated the national ban made them less likely to use ephedra products. The majority of athletes began use prior to college. Coaches, athletic trainers, and team physicians should be aware of athletes` patterns of stimulant use. Improved educational efforts directed at younger athletes are necessary to deter abuse of metabolic stimulants.